PELATIHAN PENANAMAN TANAMAN OBAT KELUARGA (TOGA) - Sumedi P Nugraha (Asian Journal of Innovation and Entrepreneurship, 2015)
Dusun Kajor Dhuwur is a one of Dusun that located in Lencoh Village, District Selo, Boyolali, Central Java Province. Mostly the residents in Dusun Kajor Dhuwur are afarmers.  Although the majority are worked as a farmer, but the residents of DusunKajor Dhuwur still don’t know about medicinal plants or also known as a livingpharmacy. A living pharmacy need to be developed because it is not only useful forcooking ingredients or for spices, but it is also useful for the alternative to protect andto nurse the healthy in natural ways without the negative effects such as ginger,turmeric, kencur, sirih, brotowali etc. Therefore, giving the training about planting the medicinal plants is one of way topreserve the cultural wisdom of medicinal plants in Indonesia, especially in the DusunKajor Dhuwur. The benefits or the efficacy of some medicinal planes will be explainedand also will be taught how to grow and use the medicinal plants.This training aims toKajor duwur residents to able to recognise and understand the benefits of traditionalmedicinal plants to protect and care the health in nature ways without the negativeeffects, decrease the family expenses with decrease the consumption in medichal drugs. The results of this training are the residents of Dusun Kajor Dhuwur know thebenefits of using medicinal plants. Beside that, the residents also know the economicvalue and the ssafe level of the medicinal plants. The residents also can reduce theconsumptions of chemical drugs that have long term effects for their body.